Phytoplankton taxonomic groups in relation to physicochemical parameters. A case study from Greek lakes (2023)
Navrozidou V., I. Nikolopoulou, S. Katsavouni, M. Seferlis, and V. Tsiaoussi. 2023. Phytoplankton taxonomic groups in relation to physicochemical parameters. A case study from Greek lakes. Poster presentation in the Symposium for European Freshwater Sciences (SEFS 13), Newcastle University, England, 18 -23 June 2023.